2018
DOI: 10.1021/acs.energyfuels.7b03265
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Reducing Emissions in Reactivity-Controlled Compression Ignition Engines by Fueling Syngas and Diesel

Abstract: A syngas/diesel dual-fuel reactivity-controlled compression ignition (RCCI) engine was numerically investigated by an improved multidimensional model coupled with a reduced chemical mechanism. In the test RCCI engine, the syngas was premixed with air in the intake manifold, while the diesel was directly injected into the cylinder well before top dead center (TDC). The effect of the syngas composition, the premixed ratio of the syngas, the initial in-cylinder temperature at intake valve closing (IVC), and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A blended fuel strategy using a mixture of fossil fuel and syngas has been studied by Ji et al, , Singh and Mohapatra, and Krishnamoorthi et al The addition of syngas can also help to improve the combustion efficiency and extend the lean burn limit . Under certain conditions, the efficient and clean combustion can be achieved. , From the above studies, it was found that the application of syngas in dual fuel mode has more potential. Despite all the results obtained, more research and optimizations are still needed to achieve better combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A blended fuel strategy using a mixture of fossil fuel and syngas has been studied by Ji et al, , Singh and Mohapatra, and Krishnamoorthi et al The addition of syngas can also help to improve the combustion efficiency and extend the lean burn limit . Under certain conditions, the efficient and clean combustion can be achieved. , From the above studies, it was found that the application of syngas in dual fuel mode has more potential. Despite all the results obtained, more research and optimizations are still needed to achieve better combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…8 Under certain conditions, the efficient and clean combustion can be achieved. 15,16 From the above studies, it was found that the application of syngas in dual fuel mode has more potential. Despite all the results obtained, more research and optimizations are still needed to achieve better combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other LTC strategies, such as homogeneous charge compression ignition (HCCI) combustion [14], and partially premixed charge (PPC) combustion [15], RCCI combustion has the advantage of combustion phasing controllability using fuel reactivity stratification [16,17]. Despite the benefits of the RCCI combustion strategy, there are still some challenging problems related to the use of this type of combustion.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the increasingly strict emission regulation, advanced combustion concepts in internal combustion (IC) engines, e.g. Reactivity Controlled Compression Ignition (RCCI), Partially Premixed Combustion (PPC), and Gasoline Compression Ignition (GCI) [2,3], are being developed for higher thermal efficiency and lower emissions. Such advanced IC engines involve high pressure and large hydrocarbon fuels where low temperature combustion (LTC) process plays an important role.…”
Section: Introductionmentioning
confidence: 99%